Xianglian pill modulates gut microbial production of succinate and induces regulatory T cells to alleviate ulcerative colitis in rats. (1st March 2023) - Liu, Chang-Shun; Hu, Yin-Xia; Luo, Zhen-Ye; Qiu, Chuan-Wei; Deng, Xiang-Hua; Chen, Fei-Long
Abstract: Ethnopharmacological relevance: Xianglian pill (XLP), a traditional Chinese formula, is widely used as treatment for ulcerative colitis (UC) in China. However, the mechanism of its therapeutic effect is still unclear. Aim of the study: Our previous studies showed a low oral bioavailability and a predominant distribution of major XLP ingredients in the gut. In the present study, we aimed to explore the mechanism of action of XLP on UC with respect to the regulation of gut microecology. Materials and methods: UC model rats established using 5% dextran sulfate sodium were treated with XLP. After the treatment period, bodyweight, colon length, histopathology, and inflammatory changes were evaluated. Further, changes in gut microbiota structure were detected via 16S rRNA sequencing, and microbial metabolites in feces were analyzed via a metabolomic assay. Antibiotic intervention and fecal microbiota transplantation were also employed to explore the involvement of gut microbiota, while the level of regulatory T cells (Tregs) in mesenteric lymph nodes was determined via flow cytometry. Transcriptome sequencing was also performed to determine colonic gene changes. Results: XLP alleviated colonic injury, inflammation, and gut microbial dysbiosis in UC model rats and also changed microbial metabolite levels. Particularly, it significantly decreased succinate level in the tyrosine pathway. We also observed that fecal microbiota derived from XLP-treated rats conferred resilience to UC model rats. However, this therapeutic effect of XLP on UC was inhibited by succinate. Moreover, XLP increased the level of anti-inflammatory cellular Tregs via gut microbiota. However, this beneficial effect was counteracted by succinate supplementation. Further, XLP induced the differentiation of Treg possibly by the regulation of the PHD2/HIF-1α pathway via decreasing microbial succinate production. Conclusions: Our findings indicated that XLP exerts its therapeutic effects on UC mainly via the gut microbiota-succinate-Treg differentiation axis. Graphical abstract: Image 1 Highlights: The immunoregulatory effects of Xianglian pill (XLP) in ulcerative colitis rats are transmissible through gut microbiota. XLP reduces gut microbial production of succinate. Succinate inhibits the differentiation of regulatory T cells by PHD2/HIF-1α pathway, which inhibits the therapeutic effect of XLP on ulcerative colitis.